Practicing autonomy in a local eduscape: schools, families and educational choice. Issue 3 (2nd July 2020) - Forsey, Martin
ABSTRACT: Portraying a localised educational system as part of broader global flows of policy ideas and practices emanating from multiple sources – an eduscape– the paper focuses on family practices shaped by global policy flows and the return impact of families on the translation of these policies into local school formations. Under scrutiny are the decentralising or devolutionary directives, linked so often to choice and competition, which took hold in Western jurisdictions in the 1980s, the influences of which are still strongly felt. The conceptual links spread to a mobile 'second modernity', implicating many a family in movement associated with choices they are obliged to make, and which are often correlated to family achievement and success. The observations reported here are framed conceptually by an interest in the synthesis of Beck's individualisation thesis and Bourdieusean practice approaches in order to portray and comprehend social being and social change.